Two-stage oxidation of petrogenic organic carbon in a rapidly exhuming small mountainous catchment - Wan-Yin Lien; Chih-Tung Chen; Yun-Hsuan Lee; Chih-Chieh Su; Pei-Ling Wang; Li-Hung Lin (Communications Earth & Environment)
Abstract Globally, the oxidative flux of petrogenic organic carbon rivals the drawdown by silicate weathering and burial of biospheric carbon. Where and how petrogenic organic carbon is susceptible to degradation along the short-path river-marine continuum in active orogens remains elusive. Here, we demonstrate the transformation of petrogenic organic carbon from a mountainous catchment in eastern Taiwan and its connecting submarine canyon. Our Raman analyses indicate that while highly graphitized carbon in slate/schist transformed into disordered form during soil development, the preferential elimination of disordered form was found along submarine transit. Additionally, quartz/rutile outperformed mica in protecting petrogenic organic carbon from transport abrasion and microbial degradation. Such an oxidative flux was estimated to be 20–35 metric tons of carbon per square kilometer per year, ranking among the greatest levels around the world and highlighting tectonically active islands and the surrounding marine systems as a hotspot of carbon emission.